(untitled) (Dhaka University Journal of Biological Sciences, 2014)
To study the biology of Pachliopta aristolochiae on its host plant Aristolochia indica singly laid eggs on the host plant were collected from the field and reared in the laboratory under optimum conditions of temperature (28 ± 3 °C) and relative humidity (70 ± 5% RH). Incubation period of the egg was 5.0 ± 0.6 days, larval developmental period was 11 ± 0.3 days, pre?pupal period was 0.87 ± 0.08 day, and the pupation took 12 ± 0.63 days. The length of 1st, 2nd, 3rd and 4th instar larvae were 4.0 ± 0.63, 9 ± 0.63, 22.6 ± 5.2 and 38.2 ± 4.70 mm, respectively. The feeding potential rate of 1st, 2nd, 3rd and 4th instar larvae were 11.4 ± 5.04, 29.6 ± 5.12, 51.4 ± 6.0 and 72.8 ± 4.9%, respectively. The weight of the faeces of 1st, 2nd, 3rd and 4th instar larvae were 0.012 ± 0.004, 0.047 ± 0.018, 0.0114 ± 0.023 and 0.274 ± 0.045 gm, respectively. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20090 Dhaka Univ. J. Biol. Sci. 23(2): 109-117, 2014